Adaptive advantages of appearance: predation, thermoregulation, and color of webbing built by New Zealand's largest moth. Issue 5 (7th April 2017) - Yule, Kirsty; Burns, Kevin
Abstract: Prey are often difficult to locate visually, which may help them avoid predators. However, an animal's appearance might also evolve in response to the abiotic environment. Here, we investigate the processes that determine the appearance of silk webbing built by New Zealand's largest endemic moth Aenetus virescens (Lepidoptera: Hepialidae), whose larvae burrow into the trunks of native trees. Larvae cover tunnel entrances with silk webbing, detritus, and epiphytes, giving them a similar appearance to tree bark. First, we conducted spectral analyses of webbing and background bark in avian tetrahedral color space to test whether webbing made larvae less visible to predatory parrots. Next, we manipulated the spectral contrast of webbing and background bark and assessed its effect on predation by parrots for over 2 yr. Last, we measured the effect of webbing on tunnel temperatures and quantified how temperatures within tunnels affected larval growth. Results indicate that webbing made larvae less visible to predatory parrots. However, webbing contrast to background bark did not affect predation by parrots. Instead, webbing increased temperatures within tunnels and facilitated more rapid larval growth. Overall results indicate that the appearance of organisms that are difficult to locate visually may not always result from selection by predators.